L’esercizio della potestà giudiziaria del fedele laico attraverso il prisma della Potestas gubernandi in Ecclesia. Sollecitazioni teologiche e canonistiche per una “Chiesa in uscita” (Stato, Chiese e pluralismo confessionale, 2018)
SOMMARIO: 1. Premessa - 2. Fondamenti teorici della posizione del fedele laico nella Chiesa - 3. Riflessioni teologiche sulla potestas sacra nella Chiesa. Il concetto di ministerialità come spazio di inserimento per il Christifidelis nella missione ecclesiale - 4. Risvolti giuridici nell’ottica di una complementarietà tra munus e potestas - 5. Mitis Iudex Dominus Iesus e aperture a una più effettiva partecipazione del fedele laico alla potestà giudiziaria - 6. Giudice unico laico e collegio di laici: prospettive de iure condendo per un’esegesi evolutiva del can. 1421, § 2, C.i.c. - 7. Rilievi conclusivi: alcune potenzialità inespresse del Mitis Iudex Dominus Iesus?The exercise of the judicial power by the lay faithful through the prism of Potestas gubernandi in Ecclesia. Theological and canonical solicitations for an “outgoing Church”ABSTRACT: The more than thirty years since the II Vatican Council and the recent procedural reforms initiated by Pope Francis make very topical a reflection on the actual role that lay faithful can exercise within the Church. In particular, by virtue of the Sacrament of Baptism, that makes everyone “sons in the Son”, it seems ecclesiologically inconceivable that lay faithful can still suffer limitations from the point of view of participation in judicial power, especially in perspective of a now-acquired theory of potestas sacra, which, altough it all comes from God, does not require, for each office, the Sacrament of holy Order. The requirements of technical preparation and knowledge of law, the only parameters on which the ecclesiastical authority must be based on the choiche of the judges, impose a re-updating of the can. 1421, § 2, C.i.c. This norm is the only one that deals, in a very limited way, with the figure of the lay judge. Just the recent reform of Mitis Iudex Dominus Iesus, also considering the synodal context in which it has born, would be well matched with an inclusive re-evaluation of the lay faithful in exercise of a ministeriality which is nothing but a concrete expression of the participation to the only mission of the which all the People of God must become executor through the times.